Sociodemographic and healthcare profile of tribal people in Bandipur tiger reserve area, Mysore, Karnataka, India - Siddalingappa, Hugara; Hoogar, Varsha; D., Sunil Kumar; T. S., Pradeep; M., Renuka (International Journal Of Community Medicine And Public Health, 2016)
Background: Tribal health and problems faced by tribal people is one of the major public health concerns in our country which has large forest belt and variety of tribes residing amongst it. In the name of wild life conservation, most of the tribes have been shifted out of the forest. This study is conducted to know social and health problems of these tribals. Methods: Cross sectional Community based descriptive study was conducted in tribal Hamlets around the Bandipur tiger reserve area of Mysore District between September 21st to 25th 2015. All the tribal population residing in the seven selected hamlets were included in the study. Descriptive statistics like percentage and mean, SD were used to describe the variables. Chi square test was used to find the significance of difference. Results: Jenukuruba and was predominant tribe in 4 hamlets, soligas in 2 and kadukuruba in 0ne. 60% of the families were nuclear. 48% were nonliterate, underfive female sex ratio was more than 1000(1285/1000males). 71% of the marriages were child marriages. And child marriages were significantly more among girls. Dependency ratio was 21.6%. Only one hamlet had accessibility to basic medicines. Mean distance for PHC was 5km and delivery facility at 28.8km (SD 7km). All hamlets had anganwadis but one centre had no anganwadi worker appointed. Immunization coverage was good but smoking and alcoholism was a major problem. Conclusions: Ongoing efforts of the Government to bring tribals to the mainstream society has a long distance to cover as only bare minimum facilities are provided to the tribals and the hesitation of tribals to accept these facilities is a challenge.